Postmodernity, the Dark Ages (London Journal of Research In Humanities and Social Sciences, 2023)
The history of humanity is a process marked by several stages. After these historical steps are thoroughly analyzed and observed they receive an inscription according to their respective characteristics. At postmodernity would not be different, despite its starting, already has deep marks that will be forever etched. It discussed one of them their main features that way more specifically. The suppression of objective values and the emergence of subjective values.
Keywords: postmodernity; objective values; subjective values; history.